State Intervention and Fuel Market Policy in Indonesia: Evaluating Justice and Maṣlaḥah through the Lens of Maqāṣid al-Sharīʿah - Alifarichsa, Muhammad Firhan; Ismatul Khayati (Jurnal Internasional Ekonomi Islam, 2025)
Introduction:  Fuel market governance plays a critical role in sustaining economic stability and social welfare in Indonesia. State intervention through fuel import restrictions has been framed as a strategy to strengthen national energy security. Nevertheless, such intervention has generated ethical concerns related to fuel quality, market transparency, and consumer protection when examined from the perspective of Islamic economics. Objective:  This study aims to evaluate the extent to which Indonesia’s fuel market policies conform to the principles of justice (ʿadl) and public welfare (maṣlaḥah ʿāmmah) within the framework of maqāṣid al-sharīʿah. Method: The research adopts a qualitative, literature-based approach that integrates normative Islamic economic analysis with secondary data from policy documents, official energy reports, and prior academic studies. a comparative analysis of fuel market governance in Malaysia and Saudi Arabia is also employed. Results:  The findings indicate that state intervention may undermine key maqāṣid objectives, particularly the protection of wealth (ḥifẓ al-māl) and life (ḥifẓ al-nafs). In contrast, transparent regulation, selective subsidies, and governance inspired by hisbah principles demonstrate more substantial alignment with maqāṣid al-sharīʿah. Impact: This study provides ethical guidance for policymakers and enhances public awareness, particularly among Muslim communities, of justice-oriented energy governance